Retailer compliance with energy label regulations - Corinne Faure; Joachim Schleich; Barbara Schlomann (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2013)
With the Framework Directive 92/75/EEC on Energy Labelling of Household Appliances, the European Union introduced a labelling system that applies to major household appliances. The EU Directive requires manufacturers to provide the data strip (accurate product energy consumption information) with each appliance to the retailers. Retailers are compelled to provide all the appliances displayed in salesrooms with complete energy labels placed on top or front of the appliance in original size and colour and clearly visible (Directive 92/75/EEC). Retailers therefore play a crucial role in the implementation of the European energy label program. Surprisingly however, their role in the success of the program has not received any attention so far. In this paper, we first develop a theoretical framework to explain retailers' compliance with the Directive. The framework comprises instrumental motives for compliance like perceived costs and benefits of compliance as well as normative motives like internalization of regulation or social pressure to comply. These factors are moderated by retailers' ability to comply. Second, we test this framework econometrically on a sample of ca. 100,000 appliances from close to 1,400 retail stores in 27 European countries. Two sets of data were collected in each store: a compliance audit and a standardized survey of store managers. For the compliance audit, researchers noted for each household appliance available in the stores whether the energy label information was available, complete, and placed as required. The survey included perceptual measures of external and internal monitoring, manufacturer compliance, effort to comply, and consumer acceptance of labels. Using as dependent variable the share of completely labelled appliances per retailer - either at the aggregate level or per product category - estimation results of fractional logit models suggest that normative motives generally appear stronger than instrumental ones.
urn:nbn:de:0011-n-2776943
Keywords: 330; energy label; compliance; household appliances; retailer